Soil analysis as the foundation of precision nutritive supply in the Hajdúszoboszló region - Víg, Róbert; Dobos, Attila; Pongrácz, Zoltán (Acta Agraria Debreceniensis, 2007)
Larger cultivated plots are heterogeneous from a pedological aspect. Heterogeneity causes problems during fertilization and harvest. The heterogeneity of cultivated areas can be compensated by fertilization which is based on soil analysis. We carried out research into the changes of the soil on three soil types, from 1966 to 2006, on the cultivated areas of Hajdúszoboszló. There were no significant changes in pH on chernozem meadow soil and meadow chernozem soil, but the pH increased in 0-30 cm layer on type meadow solonetz soil. The saline content decreased in every examined soil type. Decrease was the largest on meadow solonetz soil. Decline of humus content was the largest (0.95%) on chernozem meadow soil, and the smallest (0.39%) on meadow chernozem soil. The nitrogen content decreased with 528 ppm in the 0-30 cm layer on chernozem meadow soil, and decreased by 186 ppm on meadow solonetz soil. Phosphorus and potassium content increased in every examined soil types. Rise of phosphorus content was 188.9 ppm in the 0-30 cm layer on meadow chernozem soil. The potassium content rose by 153.7 ppm on this soil type. Phosphorus content increased with 70.8 ppm, and potassium content increased by 57.6 ppm from 1966 to 2006.